Optimization of Village Funds for Sustainable Tourism Development (Tourism Village Development Study in Indonesia ) - Bakti, Surya (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Optimizing the use of village funds has the main objective of increasing the welfare of rural communities through infrastructure development, economic empowerment, public services, and other programs that support holistic village development and also village tourism management. Sustainable tourism has become an important sector in the Indonesian economy. Sustainable tourism makes a major contribution to economic growth, job creation and national income. Over the last decade, interest in studying the impact of sustainable tourism development on economic growth has increased (León-Gómez et al., 2021). This type of research, in this study the method used is a literature study approach. The number of Indonesian tourist villages is 7,275 (Wirdayanti et al., 2021). When compared with the number of villages in Indonesia, there are 83,794 villages. This proves that there are still many opportunities for villages to continue to grow and develop into tourist villages by utilizing and optimizing village funds for sustainable village natural tourism to support the village economy.